PENGARUH PSIKOLOGI OLAHRAGA TERHADAP MENTAL PEMAIN BOLA VOLI DI DESA NANGKA - Helmi Ferdiansyah; Dicky Reva Apriana Sanga Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Sports psychology is a science that studies psychological factors that can influence a person's mentality and performance when exercising. This research aims to determine whether or not there is an influence of sports psychology on the mentality of volleyball players in Nangka Village. The method used in this research is a quantitative method in the form of an experiment with a pre-experimental design type. Researchers used this method because in this study there were no control variables and the samples used in this study were obtained based on conditions determined by the researcher. The data analysis technique for this research uses a scoring system. Based on the results of the validity test, it shows that the results of the questionnaire on the influence of sports psychology on the mentality of volleyball players, almost all of the items were declared valid, but there were 3 statement items that were invalid. So a total of 22 question items about the influence of sports psychology on the mentality of volleyball players were used in this research. Based on the SPSS processing results, the reliability test shows that the results of the reliability test using Cronbach Alpha obtained a value of a=0.985 (>0.361), meaning that the questionnaire was declared reliable.